2021
DOI: 10.3389/fcell.2020.618652
|View full text |Cite
|
Sign up to set email alerts
|

Export Control: Post-transcriptional Regulation of the COPII Trafficking Pathway

Abstract: The coat protein complex II (COPII) mediates forward trafficking of protein and lipid cargoes from the endoplasmic reticulum. COPII is an ancient and essential pathway in all eukaryotes and COPII dysfunction underlies a range of human diseases. Despite this broad significance, major aspects of COPII trafficking remain incompletely understood. For example, while the biochemical features of COPII vesicle formation are relatively well characterized, much less is known about how the COPII system dynamically adjust… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
4
1

Citation Types

1
13
0

Year Published

2022
2022
2024
2024

Publication Types

Select...
5
2
1

Relationship

0
8

Authors

Journals

citations
Cited by 14 publications
(14 citation statements)
references
References 195 publications
1
13
0
Order By: Relevance
“…We have shown that several genes and gene sets with known links to NTDs are dysregulated in placentae from fetuses with isolated SB. The COPII pathway was downregulated in case placentae and is a critical regulator of forward trafficking of proteins and lipids from the ER 32 . Disruptions in COPII‐mediated vesicular ER‐to‐Golgi transport have been linked to SB via the transporting role of COPII 33 .…”
Section: Discussionmentioning
confidence: 99%
“…We have shown that several genes and gene sets with known links to NTDs are dysregulated in placentae from fetuses with isolated SB. The COPII pathway was downregulated in case placentae and is a critical regulator of forward trafficking of proteins and lipids from the ER 32 . Disruptions in COPII‐mediated vesicular ER‐to‐Golgi transport have been linked to SB via the transporting role of COPII 33 .…”
Section: Discussionmentioning
confidence: 99%
“…We have shown for the first time that several genes and gene pathways with known links to NTDs are dysregulated in placentae from fetuses with isolated SB. The COPII pathway, which was downregulated in case placentae, is a critical regulator of forward trafficking of proteins and lipids from the endoplasmic reticulum (ER) 56 . Disruptions in COPIImediated vesicular ER-to-Golgi transport have been linked to SB via the role of COPII in transporting key components of the planar cell polarity (non-canonical Wnt) pathway [57][58][59] .…”
Section: Discussionmentioning
confidence: 99%
“…A glycoproteome analysis recently identified 55 O-mannosylation sites in Sed4 as well as 15 O-mannosylation and one N-glycosylation sites in Sec12 ( Neubert et al, 2016 ). Recent studies have demonstrated the importance of post-translational modifications in the regulation of COPII proteins, such as phosphorylation and O-glycosylation in the cytosol ( Bisnett et al, 2021 ). However, the functions of glycosylation of Sed4 and Sec12 are unknown.…”
Section: Introductionmentioning
confidence: 99%